Evolution of statin prescribing 1994–2001: a case of agism but not of sexism?. Issue 4 (1st April 2003) - DeWilde, S; Carey, I M; Bremner, S A; Richards, N; Hilton, S R; Cook, D G
Abstract : Objective: To study trends in the use of lipid lowering drugs in the UK, and to assess which patient factors influence prescribing. Methods: Routinely collected computerised medical data were analysed from 142 general practices across England and Wales that provide data for the Doctors' Independent Network database. Subjects included were people aged 35 years or more with treated ischaemic heart disease, averaging annually over 30 000. The temporal trend from 1994 to 2001 in prescription of lipid lowering drugs and daily statin dose and the odds ratios (ORs) for receiving a statin prescription in 1998 were examined. Results: Lipid lowering drug prescribing increased greatly over time, entirely because of statins, so that in 2001 56.3% of men and 41.1% of women with ischaemic heart disease received lipid lowering drugs. However, 33% of these patients were on a < 20 mg simvastatin daily equivalent. In 1998 the OR for receiving a statin fell from 1 at age 55–64 to 0.64 at 65–74 and 0.16 at 75–84 years. The age effect was similar in those without major comorbidity. Revascularised patients were much more likely to receive a statin than those with angina (OR 3.92, 95% confidence interval (CI) 3.57 to 4.31). Men were more likely to receive a statin than women (OR 1.62, 95% CI 1.54 to 1.71) but this difference disappeared after adjustment for age and severity of disease (OR 1.06). Geographical region had little effect but there was a very weak socioeconomic gradient. Conclusions: Although prescribing has increased, many patients who may benefit from lipid lowering drugs either do not receive it or are undertreated, possibly because of lack of awareness of the relative potency of the different statins. Patients with angina and the elderly are less likely to receive treatment that may prevent a coronary event.